Poetry - Constantine, David, 1944- (Oxford : Oxford University Press, 2013)
David Constantine argues that poetry matters. It matters for individuals and for the society they are members of. He asserts that poetry is not for the few but for the many, and belongs and can only thrive among them, speaks of and to their concerns.
Includes bibliographical references and index.
Keywords: Poetics; Poetry -- Social aspects; Poetry -- Translating